THE IMPACT OF ENGLISH ON INTERNATIONAL COLLABORATION IN TECHNICAL FIELDS - SOLIEV MIRZOKHID MUSOEVICH (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the era of globalization, international collaboration has become a fundamental characteristic of technical and scientific development. Engineers, researchers, and technical specialists increasingly cooperate across national borders to implement complex projects, exchange knowledge, and promote innovation. In this global environment, English has emerged as the dominant language of communication. The widespread use of English in scientific publications, international standards, multinational corporations, and digital platforms has significantly shaped the structure and efficiency of technical cooperation. This article examines the impact of English on international collaboration in technical fields. It explores the role of English as a lingua franca in research dissemination, multinational engineering projects, professional mobility, and global standardization. The paper also considers challenges related to linguistic inequality and the importance of English education in technical institutions. The study concludes that English functions as a strategic tool that enhances coordination, accelerates innovation, and strengthens international integration in technical disciplines.